Managerial Attributes and Executive Compensation - Graham, John R.; Li, Si; Qiu, Jiaping (Review of Financial Studies, 2012)
We study the role of firm- and manager-specific heterogeneities in executive compensation. We decompose the variation in executive compensation and find that time-invariant firm and, especially, manager fixed effects explain a majority of the variation in executive pay. We then show that in many settings, it is important to include fixed effects to mitigate potential omitted variable bias. Furthermore, we find that compensation fixed effects are significantly correlated with management styles (i.e., manager fixed effects in corporate policies). Finally, the method used in the article has a number of potential applications in financial economics. The Author 2011. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oup.com., Oxford University Press.